Different Effects of Giving Myofascial Release 90 Seconds and Myofascial Release 300 Seconds in Reducing Myofascial Pain Syndrome in the Upper Trapezius Muscle - Abdullah, Arif; Pristianto, Arif (Gaster, 2024)
Background Neck pain is the most common complaint and is often encountered in Indonesian society, especially among workers with static neck postures. One of them is a batik craftsman, whose sedentary position causes pain, especially in the upper trapezius area, which is often called Myofascial Pain Syndrome.Objective The aim is to find out how 90 second myofascial release and 300 second myofascial release differ in terms of reducing myofascial pain syndrome in the trapezius muscle. Methods The research used a quasi-experiment involving two groups. This research involved Laweyan batik craftsmen using a sample of 30 respondents. then divided into two groups and given myofascial release for 90 seconds and 300 seconds. Each subject experienced 25 treatment sessions, each carried out 5 times a week for 5 weeks. The evaluation carried out includes pre and post using the Neck Disability Index (NDI). Result The research results of a p-value of 0.027 using the Mann-Whitney test indicate that myofascial release for 90 seconds and 300 seconds is significantly different in reducing myofascial pain syndrome after the upper trapezius muscle. Conclusion From the results of this research it can be concluded giving Using the myofascial release technique for 300 seconds has an impact on improving muscle strength recovery, and giving myofascial release for 90 seconds has a different impact on reducing upper trapezius muscle pain.